Amyloid-Like Protein Aggregates A New Class of Bioinspired Materials Merging an Interfacial Anchor with Antifouling - Hu, Xinyi (Advanced materials (Deerfield Beach, Fla.), 2020)
© 2020 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.